A Long History of Faith‐Based Welfare in Australia: Origins and Impact1. (23rd March 2016) - Swain, Shurlee
Abstract : In a nation where governments and churches have collaborated in the delivery of welfare services since 1788, such faith‐based welfare was seen as normative rather than problematic. Indeed most Australians would struggle to imagine a welfare system that was not built on such an arrangement. However, by the late twentieth century, the world views and ideologies of church leaders and politicians were no longer in alignment, creating tensions in the relationship. This article explores the origins and development of church–state collaboration in the delivery of welfare, and examines the impact this has had on both the shape of charity and the mission of the churches as faith‐based agencies are increasingly challenged in an environment in which government funding is tied to policies that potentially transgress the principles of the gospels, and victims of past welfare practices demand reparation.